Numerical Simulation on the Longitudinal Breach Process of Landslide Dams Using an Improved Coupled DEM-CFD Method - Li, Dong-yang; Zheng, De-feng; Wu, Hao; Shen, Yue-qiang; Nian, Ting-kai (Frontiers in Earth Science, 2021)
An accurate investigation of the landslide dam breach process is crucial for the understanding the breach mechanism and disaster prediction. However, the numerical research on the landslide dam breach process to date is rarely reported, especially regarding the soil-water flow coupling effect incorporated in the erosion process. This paper presents a numerical investigation on the longitudinal breach process of landslide dams via a coupled discrete element method (DEM) and computational fluid dynamics (CFD) with the volume of fluid (VOF). Moreover, a virtual sphere model is proposed to overcome the computational instability caused by the particle size approaching the mesh size. The accuracy and validity of the improved coupled method are verified using a series of single particle sedimentation cases. By employing this method, the longitudinal breach process of landslide dams featuring different materials and hydrodynamic conditions has been simulated. It is found to satisfactorily reproduce the longitudinal breach process of landslide dams including surface flow erosion, backward erosion, head-cut erosion, and water and sediment rebalance or complete breach. The effects of the inflow discharges and dam materials on the erosion process are systematically resolved. The breach flow can cause the rotation trend of particles and lead to the increase of tangential contact force at the initial stage of the dam breaching. During the breach process, both the strength and density of the force chain continue to attenuate. The results obtained from the improved coupled DEM-CFD simulations can reasonably explain the particle-fluid interaction mechanisms, physical and morphological evolution and breach process at both macroscopic and mesoscopic scales.